New species and new records of Sorolopha Lower, 1901 from China (Lepidoptera, Tortricidae, Olethreutini) - Zhao, Jingxia; Bai, Xia; Yu, Haili (Zootaxa, 2017)
Six species of Sorolopha Lower, 1901 are recorded from China. Among them, S. nanlingica, sp. nov., S. latiuscula, sp. nov., and S. singularis, sp. nov., are described as new. Sorolopha brunnorbis Razowski, 2009, S. cyclotoma Lower, 1901, and S. euochropa Diakonoff, 1973 are recorded for the first time from China. Photographs of the adults and genitalia of the new species are provided.